1999
DOI: 10.1136/bmj.319.7204.215
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of coronary heart disease risk factors in Indian, Pakistani, Bangladeshi, and European origin populations: cross sectional study

Abstract: Objective To compare coronary risk factors and disease prevalence among Indians, Pakistanis, and Bangladeshis, and in all South Asians (these three groups together) with Europeans. Results There were differences in social and economic circumstances, lifestyles, anthropometric measures and disease both between Indians, Pakistanis, and Bangladeshis and between all South Asians and Europeans. Bangladeshis and Pakistanis were the poorest groups. For most risk factors, the Bangladeshis (particularly men) fared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
479
2
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 527 publications
(529 citation statements)
references
References 16 publications
46
479
2
2
Order By: Relevance
“…Participants were sampled from general practitioner registers or health centres and community hospital registries. 12,[14][15][16][17][18] Two studies used samples from a population or community register. 20,21 One study used samples from areas as identified by the postcode directory.…”
Section: Overview Of Methods Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants were sampled from general practitioner registers or health centres and community hospital registries. 12,[14][15][16][17][18] Two studies used samples from a population or community register. 20,21 One study used samples from areas as identified by the postcode directory.…”
Section: Overview Of Methods Of Included Studiesmentioning
confidence: 99%
“…17,18 Three studies reported on multiple South Asian subgroups (Indian, Pakistani, Bangladeshi) separately, 18,22,23 others reported only one subgroup or a combined South Asian population. [14][15][16][17]19,20,26 Most studies used Hawksley random zero sphygmomanometers to measure BP, 15,16,19 whereas two studies used mercury, 18,21 or automated devices such as the Omron (OMRON, Omron Matsusaka Co. Ltd, Kyoto, Japan), Dinamap 8100 (GE Healthcare, Critikon, FL, USA) and Roche (F Hoffmann-La Roche Ltd., Basel, Switzerland) sphygmomanometers. 12,17,20,23 Subjects were seated and quiet for at least 5 min before BP measurement.…”
Section: Overview Of Methods Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations